A junior marketing management student was adjudged one of the winners of the first annual search for outstanding marketing students - Pelayo, Josenia (Animo Repository, 1987)
Josenia Pelayo, a junior Marketing Management student was adjudged one of the winners of the First Annual Search for Outstanding Marketing students, conducted by the Philippine Marketing Association in cooperation with the Federation of Junior Marketing Association. The awards given for the first time, encouraged more young men and women to specialize in marketing.